Disastrous discretion: Ambiguous decision situations foster political favoritism - Stephan A. Schneider; Sven Kunze (ETH Zurich, KOF Swiss Economic Institute, 2021)
Allocation decisions are vulnerable to political influence, but it is unclear in which situations politicians use their discretionary power in a partisan manner. We analyze the allocation of presidential disaster declarations in the United States, exploiting the spatiotemporal randomness of all hurricane strikes from 1965-2018. We show that biased declaration behavior is not politically affordable if a disaster is either very strong or weak, when relief provision is clearly necessary or not. However, in ambiguous situations, after medium-intensity hurricanes, presidents favor areas governed by their co-partisans. Our nonlinear estimations demonstrate that this hump-shaped alignment bias exceeds average estimates up to eightfold.
hdl:20.500.11850/468932
Keywords: D72; H30; H84; P16; Q54; 330; disaster relief; distributive politics; hurricanes; natural disasters; nonlinearity; party alignment; political influence; political economy